EXPLAINING THE GENDER GAP IN CRIME: THE ROLE OF HEART RATE1. Issue 2 (6th April 2017) - CHOY, OLIVIA; RAINE, ADRIAN; VENABLES, PETER H.; FARRINGTON, DAVID P.
Abstract : Although it is well established that males engage in more crime compared with females, little is known about what accounts for the gender gap. Few studies have been aimed at empirically examining mediators of the gender–crime relationship in a longitudinal context. In this study, we test the hypothesis that a low resting heart rate partly mediates the relationship between gender and crime. In a sample of 894 participants, the resting heart rate at 11 years of age was examined alongside self‐reported and official conviction records for overall criminal offending, violence, serious violence, and drug‐related crime at 23 years of age. A low resting heart rate partially mediated the relationship between gender and all types of adult criminal offending, including violent and nonviolent crime. The mediation effects were significant after controlling for body mass index, race, social adversity, and activity level. Resting heart rate accounted for 5.4 percent to 17.1 percent of the gender difference in crime. This study is the first to produce results documenting that lower heart rates in males partly explain their higher levels of offending. Our findings complement traditional theoretical accounts of the gender gap and have implications for the advancement of integrative criminological theory.